2010
DOI: 10.1093/sleep/33.8.1091
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Neck Myoclonus During Routine Polysomnography

Abstract: Neck myoclonus is common during REM sleep and more frequent in younger individuals. This could indicate that neck myoclonus during REM sleep is a physiological phenomenon. If there is a cut-off distinguishing normal from excessive has to be investigated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 16 publications
4
36
2
Order By: Relevance
“…We found that SRHJs are less frequently associated with REMs (14.8%) then in the report of Frauscher et al. (65.7%) (Frauscher et al., ). This suggests that the network implicated in generating SRHJ probably is not the same that regulates the oculocephalic synergy during wakefulness.…”
Section: Discussioncontrasting
confidence: 44%
See 4 more Smart Citations
“…We found that SRHJs are less frequently associated with REMs (14.8%) then in the report of Frauscher et al. (65.7%) (Frauscher et al., ). This suggests that the network implicated in generating SRHJ probably is not the same that regulates the oculocephalic synergy during wakefulness.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, Frauscher et al. () found that only 20% of the events were accompanied by an arousal, while we found that about 60% of them were associated to an arousal or even to an awakening in 20% of the cases (Frauscher et al., ). These discrepancies could be explained by (a) the difference in the time window used to assess the associations which has not be specified in previous reports, (b) by the fact that Frauscher et al.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations